Little Lord Fauntleroy - Burnett, Frances Hodgson, 1849-1924.; Rust, Graham (Ware, Hertfordshire : Wordsworth Editions ltd., 1994)
An American boy goes to live with his grandfather in England where he becomes heir to a title and a fortune.
Keywords: Grandfathers -- Fiction; Great Britain -- History -- 19th century -- Fiction